1991
DOI: 10.1002/jcp.1041490302
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide‐induced oxidative stress to the mammalian heart‐muscle cell (cardiomyocyte): Lethal peroxidative membrane injury

Abstract: Oxidative stress induced by hydrogen peroxide (H2O2) may contribute to the pathogenesis of ischemic-reperfusion injury in the heart. For the purpose of investigating directly the injury potential of H2O2 on heart muscle, a cellular model of H2O2-induced myocardial oxidative stress was developed. This model employed primary monolayer cultures of intact, beating neonatal-rat cardiomyocytes and discrete concentrations of reagent H2O2 in defined, supplement-free culture medium. Cardiomyocytes challenged with H2O2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(33 citation statements)
references
References 103 publications
1
31
0
1
Order By: Relevance
“…Different conditions of oxidative status were obtained by preparing DHA solutions in the presence of an antioxidant, 1 mM α-tocopherol [27], or a pro-oxidant, 1 mM H 2 O 2 [28]. Bathing isolated mouse ventricular cardiomyocytes for 20 min in DHA prevented arrhythmias, which concurs in part with a previous report [11].…”
Section: Dha Under Oxidative Stress Conditions Reduced Cardiac Arrhytmentioning
confidence: 73%
“…Different conditions of oxidative status were obtained by preparing DHA solutions in the presence of an antioxidant, 1 mM α-tocopherol [27], or a pro-oxidant, 1 mM H 2 O 2 [28]. Bathing isolated mouse ventricular cardiomyocytes for 20 min in DHA prevented arrhythmias, which concurs in part with a previous report [11].…”
Section: Dha Under Oxidative Stress Conditions Reduced Cardiac Arrhytmentioning
confidence: 73%
“…It has been reported that during myocardial necrosis theses enzymes are released from the heart to bloodstream [43]. Also, reactive oxygen species (ROS) cause membrane injury by initiating lipid peroxidation that results in loss of function and integrity of myocardial membranes [44]. This hypothesis is confirmed by the data presented in this study and demonstrated that CP increased TBARS, an index of lipid peroxidation, and decreased GSH, SOD, GSHPx, and CAT, an index of antioxidant defense mechanism, in cardiac tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The change in leakage of LDH reflects damage to the myocardial cell membrane, and the increase in its content is usually regarded as the symbol of irreversible injury to cardiomyocytes [24]. MDA is a product of lipid peroxidation, and its content can reflect the degree of lipid peroxidation in the cell membrane and the severity of damage to cells by free radicals [25].…”
Section: Discussionmentioning
confidence: 99%